2018
DOI: 10.3168/jds.2017-13851
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding milk replacer at 2 rates with pelleted, low-starch or texturized, high-starch starters on calf performance and digestion

Abstract: Milk replacer (MR) feeding programs have traditionally fed at less than ad libitum amounts to promote calf starter (CS) intake and allow early weaning. More recently, increased amounts of MR preweaning have been shown to increase preweaning ADG, although postweaning growth may be reduced. Several studies suggest that limited postweaning digestion of nutrients in CS may contribute to postweaning growth impairment. It is not clear whether CS formulation might also contribute to differences in postweaning nutrien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
58
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 52 publications
(76 reference statements)
6
58
3
Order By: Relevance
“…Furthermore, the range of weaning practices used on farms indicates that there is a lack of consistent guidance regarding the best way to wean calves, or if there is, it is not being consistently implemented at farm level. Research has largely focused on the positive effects of gradual weaning based on concentrate intakes [66] and the effect of pre-weaning milk or CMR allowances on the weaning and post-weaning period [67]. However, participants were unsure of the best weaning methods, largely pondering whether transition should be done by diluting milk feeds, reducing the number of feeds, or reducing the quantity fed at each meal.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the range of weaning practices used on farms indicates that there is a lack of consistent guidance regarding the best way to wean calves, or if there is, it is not being consistently implemented at farm level. Research has largely focused on the positive effects of gradual weaning based on concentrate intakes [66] and the effect of pre-weaning milk or CMR allowances on the weaning and post-weaning period [67]. However, participants were unsure of the best weaning methods, largely pondering whether transition should be done by diluting milk feeds, reducing the number of feeds, or reducing the quantity fed at each meal.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, the disap-pearance of starch in the digestive tract was essentially complete. Quigley et al (2019a, b) conducted an analysis of 3 studies (Hill et al, 2016b;Dennis et al, 2018a;Quigley et al, 2018) using individual digestibility measurements (n = 207). Multiple modeling approaches were used (Quigley et al, 2019a), including linear mixed models, exponential models, and broken-line regression models.…”
mentioning
confidence: 99%
“…Calves weaned abruptly from high amounts of MR often have eaten little CS before weaning. Rapid increases in CS intake following weaning in these calves do not allow for proper nutrient utilization as rumen development was insufficient to allow the calf to extract sufficient ME from the CS as predicted by the NRC (Dennis et al, 2018a;Quigley et al, 2018). Quigley et al (2019b) calculated that 15 kg of cumulative NFC was needed for sufficient digestive maturation to allow the calf to obtain ME from CS.…”
mentioning
confidence: 99%
“…Controversial results have been reported regarding the effects of different grain sources on the intake in dairy calves [ 3 , 11 , 30 ]. Different processing methods [ 3 , 15 ] could significantly influence the intake through ruminal pH alterations. Khan et al [ 3 ] reported that lower ruminal pH in the calves fed on BG depressed intake.…”
Section: Discussionmentioning
confidence: 99%
“…However, high levels of BG are commonly incorporated in rations of dairy cows [ 9 ], fattening bulls [ 10 ], and dairy calves [ 3 , 11 ]. Optimum dietary particle size [ 12 ], adequate level of forage in the diet [ 13 , 14 ], and proper fermentation rate of starch [ 15 ] are major factors influencing the feeding efficiency of high-starch grains in dairy calves.…”
Section: Introductionmentioning
confidence: 99%